Glyphosate afeta parâmetros fisiológicos e nutricionais em soja RR e RR2 - Zobiole, Luiz Henrique Saes (2011)
Problems caused by the herbicide glyphosate on soybean glyphosate-resistant (RR soybean) are a current topic, mainly those related to the higher incidence of diseases, to the mineral nutrition and to the effect on beneficial soil microorganisms. However, the majority of these studies have so far neglected possible negative effects related to nutrition, growth and development of RR soybean. With the continuous increased of RR soybean area in the world, many farmers have reported injury symptoms in some varieties of RR soybean after the use of glyphosate. Results obtained in this study revealed that the injuries caused by glyphosate in RR soybean may be related to the decrease in photosynthetic parameters. Beyond the photosynthetic damage, glyphosate also affected the water use efficiency of RR soybean, with significative decrease on the conversion of the photoassimilates. The "second generation" of cultivars RR soybean ("RR2"), to glyphosate injury, had the same visual injuries as the previous RR soybean, as well as, significative decreases on nutrient uptake and photosynthesis under glyphosate treatments. The glyphosate effects were more pronounced with increased glyphosate rates and late applications for both soybean RR and RR2.